The Mechanism of Ammonia-Assimilating Bacteria Promoting the Growth of Oyster Mushrooms (Pleurotus ostreatus) - Rui Li; Qi Zhang; Yuannan Chen; Yuqian Gao; Yanqing Yang; Qin Liu; Weili Kong; Haopeng Chai; Bingke Sun; Yanan Li; Liyou Qiu (Journal of Fungi)
Oyster mushrooms (Pleurotus ostreatus) are one of the most commonly grown edible mushrooms using compost, which contains high concentrations of ammonia. In this study, inoculation of the oyster mushroom culture substrate with ammonia-assimilating bacterium Enterobacter sp. B12, either before or after composting, reduced the ammonia nitrogen content, increased the total nitrogen content of the compost, and enhanced the mushroom yield. Co-cultivation with P. ostreatus mycelia on potato dextrose agar (PDA) plates containing 200 mM NH4+, B12 reduced reactive oxygen species (ROS) accumulation in the mycelia and downregulated the expression of the ROS-generating enzymes NADPH oxidase A (NOXA) and the stress hormone ethylene synthase 1-aminocyclopropane-1-carboxylate oxidase (ACO). It also downregulated the expression of the ammonia-assimilating related genes in the mycelia, such as glutamate dehydrogenase (GDH), glutamate synthase (GOGAT), glutamine synthetase (GS), ammonia transporter protein (AMT), and amino acid transporter protein (AAT), while upregulating its own ammonia-assimilation genes. These findings suggest that the mechanism by which B12 promoted oyster mushroom growth was that B12 assimilated ammonia, alleviated ammonia stress, mitigated ROS accumulation in the mycelia, and supplied ammonia and amino acids to the mycelia. To our knowledge, ammonia-assimilating bacteria are a novel type of mushroom growth promoter (MGP).